Low Dose Colonization of Broiler Chickens With ESBL-/AmpC- Producing Escherichia coli in a Seeder-Bird Model Independent of Antimicrobial Selection Pressure - Robé, Caroline; Blasse, Anja; Merle, Roswitha; Friese, Anika; Roesler, Uwe; Guenther, Sebastian (Frontiers in Microbiology, 2019)
Extended-spectrum beta-lactamase- (ESBL-) and AmpC beta-lactamase- (AmpC-) producing Enterobacteriaceae pose a risk for both human and animal health. For livestock, highest prevalences have been reported in broiler chickens, which are therefore considered as a reservoir of multidrug-resistant bacteria. The possibility of transfer to humans either by a close contact to colonized broiler flocks or through contaminated retail meat results in the necessity to develop intervention measures for the entire broiler production chain. In this regard, a basic understanding of the colonization process is mandatory including the determination of the minimal bacterial load leading to a persistent colonization of broiler chickens. Therefore, we conducted a bivalent broiler colonization study close to real farming conditions without applying any antimicrobial selection pressure. ESBL- and AmpC- negative broiler chickens (Ross 308) were co- colonized on their third day of life with two strains: one CTX-M-15-producing Escherichia coli-ST410 and one CMY-2/mcr-1-positive E. coli-ST10. Colonization was assessed by cloacal swabs over the period of the trial, starting 24 h post inoculation. During the final necropsy, the contents of crop, jejunum, cecum and colon were quantified for the occurrence of both bacterial strains. To define the minimal oral colonization dosage 104 to 101 colony forming units (cfu) were orally inoculated to four separately housed broiler groups (each n=19, all animals inoculated) and a dosage of already 101 cfu E. coli led to a persistent colonization of all animals of the group after three days. To assure stable colonization, however, a dosage of 102 cfu E. coli was chosen for the subsequent seeder- bird trial. In the seeder- bird trial one fifth of the animals (seeder, n=4) were orally inoculated and kept together with the non- inoculated animals (sentinel, n=16) to mimic the route of natural infection. After 35 days of trial, all animals were colonized with both E. coli strains. Given the low colonization dosage and the low seeder/sentinel ratio, the rapid spread of ESBL- and AmpC- producing Enterobacteriaceae in conventional broiler farms currently seems inevitably resulting in an urgent need for the development of intervention strategies to reduce colonization of broilers during production.